2020
DOI: 10.1021/acs.jpcc.0c07068
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Fatigue Failure of Flexible Poly(9,9-dioctylfluorene-alt-benzothiadiazole) (PFBT)–ZnO Nanoparticle Hybrid Resistive Switching Memory Devices

Abstract: Polymer–nanoparticle (NP) hybrid nanocomposites act as essential elements for ultraflexible memory devices due to their processability, flexibility, and chemical resistance. However, a key limitation to their potential is associated with their mechanical reliability with the variation of temperature, which is still poorly understood. Herein, we systematically investigated the temperature-dependent fatigue failure of the Al/poly­(9,9-dioctylfluorene-alt-benzothiadiazole)–ZnO/Al/PET device, in which an 80% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the subzero temperature mechanical properties of multiwalled carbon nanotube-reinforced epoxy nanocomposites were reported by Chen et al With the temperature decreasing from room temperature to −196 °C, plasticization of the epoxy matrix and swelling-induced interfacial stresses lead to a deteriorated mechanical performance . Similarly, we previously investigated the temperature-dependent fatigue properties of the Al/poly­(9,9-dioctylfluorene-altbenzothiadiazole)–ZnO/Al/PET resistive device and demonstrated that the poor low-temperature performance was mainly caused by the large stiffness mismatch at the polymer/NP interface …”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, the subzero temperature mechanical properties of multiwalled carbon nanotube-reinforced epoxy nanocomposites were reported by Chen et al With the temperature decreasing from room temperature to −196 °C, plasticization of the epoxy matrix and swelling-induced interfacial stresses lead to a deteriorated mechanical performance . Similarly, we previously investigated the temperature-dependent fatigue properties of the Al/poly­(9,9-dioctylfluorene-altbenzothiadiazole)–ZnO/Al/PET resistive device and demonstrated that the poor low-temperature performance was mainly caused by the large stiffness mismatch at the polymer/NP interface …”
Section: Introductionmentioning
confidence: 53%
“…15 Similarly, we previously investigated the temperature-dependent fatigue properties of the Al/poly(9,9dioctylfluorene-altbenzothiadiazole)−ZnO/Al/PET resistive device and demonstrated that the poor low-temperature performance was mainly caused by the large stiffness mismatch at the polymer/NP interface. 16 On the other hand, previous research also showed that matrix backbones, such as polyurethane, rubber, hyperbranched polymer, and siloxane, are the other key factors that affect the fatigue characteristics of sensors based on MXene/polymer composites at subzero temperatures. 17−19 For instance, when the polydimethylsiloxane (PDMS) matrix was cooled down to −150 °C, the damage mode transitioned from microcrack damage caused by plastic squeeze slip to brittle fracture damage induced by the cleavage step under a quasistatic compression load, as proposed by Sun et al 19 Wang et al found that the neat epoxy matrix exhibited a slight nonlinear failure behavior at −196 °C, which was ascribed to the restrained mobility of the polymer chains due to the less free volume in the frozen epoxy network at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Upon threshold bending cycles, the delamination between NiO and ZnO functional layers restrains the injected electrons from overflowing into the GaIn electrode. [ 33 ] Meanwhile, the severe cracks cut off the conductive paths and result in permanent device break‐down. Our work clearly indicates that the RS performance is sensitive to the fracture behavior at the p‐n interface, while proper engineering stacking structure of the active layer can enhance the mechanical endurance.…”
Section: Resultsmentioning
confidence: 99%
“…The large elastic mismatch between different layers caused remaining stress, resulting in poor sensitivity of the flexible CNC film under various temperatures. [ 29 ] Therefore, the contributions of bending and temperature to structural damage were separately deliberated. Herein, all the layers were assumed to be homogeneous in the microstructure without any impurity.…”
Section: Resultsmentioning
confidence: 99%